Five-Year-olds' Acoustic Realization of Mandarin Tone Sandhi and Lexical Tones in Context Are Not Yet Fully Adult-Like - Xu Rattanasone, Nan; Tang, Ping; Yuen, Ivan; Gao, Liqun; Demuth, Katherine (Frontiers in Psychology, 2018)
Large numbers of children around the world are learning tone languages, but few studies have examined the acoustic properties of children’s early tone productions. Even more scarce are acquisition studies on tone sandhi, a tone change phenomenon which alters the surface realization of lexical tones. Two studies using perceptual coding report the emergence of lexical tone and tone sandhi at around 2 years (Hua & Dodd, 2000; Li & Thompson, 1977). However, the only acoustic study available shows that 3-year-olds are not yet adult-like in their lexical tone productions (Wong, 2012). This raises questions about when children’s productions become acoustically adult-like and how their tone productions differ from those of adults. These questions were addressed in the current study which compared Mandarin-speaking preschoolers’ (3-5-year-olds) tone productions to that of adults. A picture naming task was used with disyllabic real words familiar to preschoolers. Overall children produced appropriate tone contours for all tones, i.e. level for tone 1, rising for tones 2, 3 and full sandhi, falling for tone 4 and half sandhi. However, children’s productions were not adult-like for tones 3, 4, and the sandhi forms, in terms of coordinating pitch range, slope and curvature, with little evidence of development across ages. These results suggest a protracted process in achieving adult-like acoustic realization of both lexical and sandhi tones.